2014
DOI: 10.5751/es-06476-190142
|View full text |Cite
|
Sign up to set email alerts
|

Is Education a Key to Reducing Vulnerability to Natural Disasters and hence Unavoidable Climate Change?

Abstract: ABSTRACT. The collection of articles in this Special Feature is part of a larger project on "Forecasting Societies' Adaptive Capacity to Climate Change" (an Advanced Grant of the European Research Council to Wolfgang Lutz). In investigating how global change will affect population vulnerability to climate variability and extremes, the project aims to help develop strategies that enable societies to better cope with the consequences of climate change. In doing so, the basic hypothesis being tested is that socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 285 publications
(184 citation statements)
references
References 44 publications
(51 reference statements)
7
166
1
10
Order By: Relevance
“…Not only does it contribute towards productivity improvement (Schultz 1998;Orazem and King 2008), it is also fundamental to other factors determining development such as health (Cochrane et al, 1982;Kippersluis et al, 2011), fertility (Osili and Long, 2008;Wolpin and Todd, 2006) and civic participation (Castelló-Climent, 2008;Dee, 2004;Glaeser et al, 2007). Recent evidence has pointed that education also contributes to vulnerability reduction in the context of climate change Muttarak and Lutz, 2014). In this paper, we have shown that, in addition, formal education significantly encourages pro-environmental behaviours, which is also crucial for the reduction of carbon emissions and the promotion of environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does it contribute towards productivity improvement (Schultz 1998;Orazem and King 2008), it is also fundamental to other factors determining development such as health (Cochrane et al, 1982;Kippersluis et al, 2011), fertility (Osili and Long, 2008;Wolpin and Todd, 2006) and civic participation (Castelló-Climent, 2008;Dee, 2004;Glaeser et al, 2007). Recent evidence has pointed that education also contributes to vulnerability reduction in the context of climate change Muttarak and Lutz, 2014). In this paper, we have shown that, in addition, formal education significantly encourages pro-environmental behaviours, which is also crucial for the reduction of carbon emissions and the promotion of environmental protection.…”
Section: Discussionmentioning
confidence: 99%
“…d Proxy for human capital. It is assumed that the higher percentage of the population with higher education reduces vulnerability, therefore a negative correlation with vulnerability is assumed [36].…”
Section: Choice Of Indicatorsmentioning
confidence: 99%
“…Recent empirical studies have demonstrated consistent evidence showing that countries and communities with higher average levels of education experience lower vulnerability to natural disasters 69 . This applies to both developed and less developed countries as well as different dimensions of vulnerability including preparedness and responses to disasters, mortality, morbidity, coping strategies, recovery from disasters and other relevant outcomes.…”
Section: Education Changes Our Behaviour and Reduces Vulnerabilitymentioning
confidence: 99%
“…With the focus of this review on "dangerous" climate change, given the consistent evidence on the protective role of education in reducing disaster vulnerability 69 , we can conclude that better …”
Section: Education Changes Our Behaviour and Reduces Vulnerabilitymentioning
confidence: 99%